Patchiness in the Distribution of Planktonic Heterotrophic Bacteria in Lakes - Palmer, F. E. (1976)
By using conventional dilution plating procedures, the heterotrophic planktonic bacteria in Lake Washington were found to be distributed in small-scale (<1.0 ml) and large-scale (>1 m in horizontal distance) patches. Recommendations are made on sampling and enumeration procedures to minimize the effect of patchiness on obtaining an accurate estimate of bacterial numbers.